Analisa Future Terrorism Threat Dari Serangan Manual ke Serangan Otonom: Transformasi Strategi Terorisme di Era Drone dan Kecerdasan Buatan - Rommy Edward Pryambada (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The development of drone technology and artificial intelligence (AI) has presented great opportunities in various sectors, but at the same time opened up new loopholes for potential terrorist attacks. This article analyzes the shift in terrorism attack strategies from traditional manual methods to the use of drone-based autonomous systems and AI. Through a descriptive qualitative approach and literature review, this study explores how this technology is used to improve the effectiveness, anonymity, and scale of attacks. The study also discusses threats arising from AI-based drone swarm capabilities, potential cyberattacks on drone systems, and global regulatory lags in anticipating these threats. In addition, this article offers policy recommendations to strengthen national defense systems against the increasingly complex and automated evolution of terrorism threats. These findings are expected to be an early contribution to the development of counter-terrorism strategies that are adaptive to technological advances.